The Impact of Air Pollution on Children’s Health - Hendrickx, Hanne; van Eyck, Annelies; Lamote, Kevin; Samson, Roeland; Verhulst, Stijn (Belgian Journal of Paediatrics, 2025)
Air pollution poses a major environmental risk to our health. Particulate matter affects more people than any other pollutant and is therefore commonly used as a proxy indicator for air pollution. Children are of particular interest, since they are uniquely vulnerable to the effects of exposure to air pollution. Little is known about the effects of air pollution in healthy children as studies often focus on an adult or elderly population, or children with an underlying condition such as asthma. Additionally, the large variation in study design across available research leads to inconsistent results. This review will give an overview of existing studies on the effect of air pollution in children. Overall, evidence can be found, supporting the detrimental effects of exposure to air pollution on certain health outcomes. As such, negative associations were found between both children’s respiratory health and neurocognitive functions and exposure to air pollution. Moreover, a possible link could be unveiled between endothelial dysfunction and cardiovascular, respiratory or neurocognitive effects in response to exposure to air pollution. A future challenge remains to generalize study designs as much as possible. Acute respiratory effects, neurocognitive changes or effects on endothelial function in children in relation to PM exposure are still scarcely studied in healthy children, especially based on high resolution personal monitoring data. Furthermore, there is still insufficient evidence for causal associations.